Horta Da Vida: Uma Cartografia Entre Adolescentes Em Conflito Com A Lei E Uma Experiência Educacional - Limongelli, Rafael Moraes [UNIFESP] (2017)
The objective of this study is to produce a cartography of the teenagers in conflict with the law related with function-educator and incited by the experience “Garden of Life” realized at Unidade de Internação - Vila Leopoldina of Fundação CASA with teenagers, families, officials and teachers. For that, it’s necessary to make reference to a genealogy of discursive forces that compose the lowest (menor) and the teenager in conflict with the law (PASSETTI, 1990, 1995; SILVEIRA, 2009; AUGUSTO, 2013), as well as position that genealogy to build a cartography of the scenery which compose the social education action of Fundação CASA. That cartography is possible due to an archive built by the researcher between 2010-2012, period in which he acts as a teacher at Fundação CASA Vila Leopoldina. This study works with the theoretical reference of Foucault (1979, 1988, 1999, 2004, 2010a, 2010b), Guattari (2013), Deleuze (2006, 2007 and 2010) and Kastrup (2007). Delving into the possibilities emerged from a function-educator, we intend to posit reflections about the hypothesis of the existence of non-places within an educational experience, producing territories to the affirmation of creation and inventiveness.